Institutional Barriers to Continuous Professional Development (CPD) Programs - Ahmad, Maaz; Laraib Qamar; H.M. Owais Nasim; Rab Nawaz Lodhi; Usman Ashraf; Saeed Shafi (Journal of University Medical & Dental College, 2024)
Abstract BACKGROUND AND OBJECTIVE: Continuous Professional Development (CPD) Programs aim to support the career progression of faculty members by leveraging their professional experiences, theoretical knowledge, research, and professionalism with colleagues. These programs enhance skills, knowledge, and competencies throughout a faculty career. However, institutional barriers such as heavy workloads and limited resources can hinder the effectiveness of CPD programs. Faculty training enables them to address concerns, be aware of their teaching assumptions, and foster a positive educational environment. It requires reflection, openness to new ideas, and intellectual work for professional growth. This study’s objective was to determine the frequencies of Institutional Barriers faced by faculty to Continuous Professional Development (CPD) Programs. METHODOLOGY: In this research, we used an observational study design. Purposive sampling was employed to collect the responses. A total of 229 participants responded. Data were entered and analyzed using IBM SPSS version 26 software. A pilot study was conducted to measure reliability. Frequencies were measured, and associations between categorical variables were determined using the Pearson Chi-Square Test. RESULTS: Significant associations of almost all the identified institutional barriers were observed with academic positions whereas the majority of the barriers demonstrated no association with gender and specialty. CONCLUSION: Academic position is the most important factor identified in our study, showing strong associations with almost all the institutional barriers studied. By creating a supportive environment and promoting continuous learning, institutions can empower faculty members to engage in CPD activities and enhance their professional development.